Support for a general factor of well-being - Longo, Ylieno; Coyne, Iain; Joseph, Stephen; Gustavsson, Petter (Elsevier, 2016)
Well-being is typically defined as positive feeling (e.g. happiness), positive functioning (e.g. competence, meaning) or a combination of the two. Recent evidence indicates that well-being indicators belonging to different categories can be explained by single “general” factor of well-being (e.g. Jovanovic, 2015). We further test this hypothesis using a recent well-being scale, which includes indicators of positive feeling and positive functioning (Huppert & So, 2013). While the authors of the scale originally identified a two-factor structure, in view of recent evidence, we hypothesize that the two-factor solution may be due to a method effect of different items being measured with different rating scales. In study 1, we use data from the European Social Survey round 3 (n = 41,461) and find that two factors have poor discriminant validity and, after using a bifactor model to account for different rating scales, only the general factor is reliable. In study 2, we eliminate method effects by using the same rating scale across items, recruit a new sample (n = 507), and find that a one-factor model fits the data well. The results support the hypothesis that well-being indicators, typically categorized as “positive feeling” and “positive functioning,” reflect a single general factor.